Estimating Economic Capacity - Gift, Richard E. (Book collections on Project MUSE., 1968)
Noting the variety of methods by which the concept of economic capacity is measured and the different ways that the concept is defined, Richard E. Gift seeks here to develop a conceptual framework within which a meaningful interpretation of these many definitions and measures of productive capacity can be made. Gift's method is to show the common structure that is shared by all capacity concepts and arguments. This structure consists of a list of variables that must always be considered when assessing the economic capacity of productive equipment. He then shows that the problems which arise in.